Doktrin Inerrancy dan Identitas Kaum Injili di Indonesia: Sebuah Kritik Konstruktif - Daniel Trihandarkha (Predica Verbum: Jurnal Teologi dan Misi, 2023)
Inerrancy doctrine appeared at the late 19th century in America as an answer to the emergence of critical and literature analysist movement from Europe, especially from Germany. The challenge toward the authority of the bible had emerged since the early church father, especially toward the historical aspect of the book of Genesis. It has been a straightforward notion to link doctrine of inerrancy with the evangelical Christians. The identity of being Evangelical with inerrancy doctrine seems inseparable, ever since. However, the rapid shift in theology, politics, and culture, firstly in the West, and, secondly, around the world demands the identity and its doctrinal statement to be redefined. Theological debates and the implication toward Indonesian churches had not been impactful significantly toward Christians in non-ordained level. Nevertheless, in academic sphere the distinction between ecumenical and evangelical Christians has emerged and yet is limited in writing discourse.